Meeting the Challenge of Managing Seniors With Multiple Complex Conditions: The Central Role of Primary Care - Lee, Linda; Heckman, George A. (Canadian Geriatrics Society, 2012)
With the aging population, primary care physicians will be increasingly challenged to manage more seniors with complex chronic conditions. The North American population aged 65 years and above is projected to increase from 14% in 2009 to 24% by 2036, and, by 2050, the average life span worldwide is expected to extend another 10 years. Three quarters of seniors have one or more chronic conditions; in one Canadian study, nearly half of patients had five or more types of chronic disease. It is well established that chronic diseases contribute to disability, diminished quality of life, as well as increased health costs. Yet currently, Canadian seniors with chronic disease receive suboptimal quality of care. Most primary care physicians do not appear able to properly manage chronic illness although most of the visits for chronic conditions are provided in primary care. Continued poor management of chronic conditions is expected to have a profound impact on health system utilization and quality of life for these persons and their families. This article reviews evidence that can help to inform the development of future programs aimed at improving care for seniors with chronic illnesses.
Keywords: Frailty; Innovative practices; Emerging practices; Polymorbidity in primary care